Acute elbow dislocations in athletes - Parsons, B. O.; Ramsey, M. L. D (Clinics in Sports Medicine, 2010)
Elbow dislocation in the athletic population is not an uncommon injury. The literature does not clearly establish treatment guidelines, with treatment being extrapolated from the experience in the general population. A short period of immobilization with early range of motion exercises limits disability and allows return to sports participation within 6 weeks.